A method for detection of randomly placed objects for robotic handling. (August 2016) - Tsarouchi, Panagiota; Matthaiakis, Stereos-Alexandros; Michalos, George; Makris, Sotiris; Chryssolouris, George
Abstract: The image based systems still have open issues in order to meet the latest manufacturing requirements for simplicity, low cost as well as the limited maintenance requirements. In this direction, there is a method proposed for the recognition of 3D randomly placed objects for eventual robotic handling. The method includes a 2D vision system and is combined with data from computer-aided design (CAD) files for the generation of 3D coordinates. It is generic and can be used for the identification of multiple randomly placed objects. The method has been implemented in a software tool using MATLAB ® and has been applied to a consumer goods case for the recognition of shaver handles.